Achieving Complete Remission of Hepatocellular Carcinoma: A Significant Predictor for Recurrence-Free Survival after Liver Transplantation - Christin Bürger; Miriam Maschmeier; Anna Hüsing-Kabar; Christian Wilms; Michael Köhler; Martina Schmidt; Hartmut H. Schmidt; Iyad Kabar (Canadian Journal of Gastroenterology and Hepatology)
Background. Liver transplantation (LT) is a curative treatment for hepatocellular carcinoma (HCC) and the underlying primary liver disease; however, tumor recurrence is still a major issue. Therefore, the aim of this study was to assess predictors and risk factors for HCC recurrence after LT in patients within and outside the Milan criteria with a special focus on the impact of different bridging strategies. Methods. All patients who underwent LT for HCC between 07/2002 and 09/2016 at the University Hospital of Muenster were consecutively included in this retrospective study. Database research was performed and a multivariable regression analysis was conducted to explore potential risk factors for HCC recurrence. Results. A total of 82 patients were eligible for the statistical analysis. Independent of bridging strategy, achieving complete remission (CR) was significantly associated with a lower risk for tumor recurrence (p = 0.029; OR = 0.426, 95% CI 0.198-0.918). A maximal diameter of lesion < 3 cm was also associated with lower recurrence rates (p = 0.040; OR = 0.140, 95% CI 0.022-0.914). Vascular invasion proved to be an independent risk factor for HCC recurrence (p = 0.004; OR = 11.357, 95% CI 2.142-60.199). Conclusion. Achieving CR prior to LT results in a significant risk reduction of HCC recurrence after LT independent of the treatment modalities applied.